Comparison of a new ELISA‐based with the flow cytometric assay for vasodilator‐associated stimulated phosphoprotein phosphorylation to assess P2Y12‐inhibition after ticagrelor intake. Issue 6 (26th August 2013) - Hobl, Eva‐Luise; Jilma, Bernd; Derhaschnig, Ulla; Schoergenhofer, Christian; Schwameis, Michael; Jilma‐Stohlawetz, Petra
Abstract : Background: Ticagrelor is a P2Y12 receptor antagonist, with superior effects but also ensuing enhanced bleeding risk as compared to clopidogrel. Determination of platelet inhibition may be useful to confirm efficient platelet inhibition on an individual patient level and to identify patients at risk for bleeding. The vasodilator‐associated stimulated phosphoprotein (VASP) phosphorylation assay specifically measures platelet P2Y12 inhibition, but has so far required individual sample processing. A new ELISA‐based VASP assay has been developed, which allows batch analysis after initial platelet activation. Because of the reversible binding of ticagrelor it is unclear if the ELISA and flow cytometric assays provide comparable results; several washing steps of the ELISA may potentially result in false low results through dilution. Methods: We hypothesized that the conventional and new methods may be comparable when ticagrelor is used. We pair‐wise compared the platelet reactivity index (PRI) between assays in a prospective clinical trial. Six healthy volunteers received a single 180 mg loading dose of ticagrelor. Results: PRI‐values of the two methods correlated well ( r  = 0.97, P  < 0.001). Ticagrelor rapidly decreased PRI values on average after 50 min, but nadir levels 2–6 h after ticagrelor intake were 15% higher when PRI% was measured with the flow cytometric method. Bland‐Altman analysis showed that the flow cytometric assay measured markedly higher PRI levels than the new ELISA‐based technique (mean difference 13%). Conclusions: The new ELISA‐based VASP assay offers an alternative to the currently used flow cytometric method, but measures lower PRI levels, particularly when PRI falls below 20% after ticagrelor intake. © 2013 International Clinical Cytometry Society